Community college : - Stafford, Susan H. (Wiley, 2006)
It describes the community college experience and covers the benefits of attending a community college, how to apply, how to afford it (including the scoop on financial aid), where a community college education can lead, and more. Whether you're considering community college as a springboard to further education, a launchpad for a promising career, or a way to enhance your skills for today's competitive job market, you'll learn what to expect and what to do if you decide community college is right for you.